SUPERVISION OF THE POLICE IMPLEMENTATION OF THE REGULATION OF THE CHIEF OF POLICE OF THE REPUBLIC OF INDONESIA NUMBER 2 OF 2022: CASE STUDY OF MURDER BY POLICE IN PALANGKA RAYA - Nina Seftiana; Kiki Kristanto; Ivans Januardy (RADJA PUBLIKA, 2025)
This study aims to analyze the implementation of Inherent Supervision (Waskat) within the National Police with a case study of a murder committed by a police officer in Palangka Raya. Although the Chief of Police Regulation Number 2 of 2022 has been drafted as a guideline for internal supervision, in practice there are still gaps that allow for behavioral deviations by members of the National Police. This study uses a qualitative approach with an in-depth interview method with related parties, including members of the National Police, internal supervisors, and witnesses and the victim's family. The results of the study show that the supervision carried out is still limited to administrative and technical aspects, while ethical and moral aspects are often less considered. The case that occurred in Palangka Raya is a real example that ineffective internal supervision can damage the image of the National Police and reduce public trust in the police. This study suggests the importance of strengthening a more transparent external supervision mechanism, as well as increasing training and ethical awareness for members of the National Police to improve integrity and professionalism. Thus, more effective supervision can help create a National Police that is more accountable and trustworthy to the public.